Inhibitory effects of a major soy isoflavone, genistein, on human DNA topoisomerase II activity and cancer cell proliferation - MIZUSHINA, YOSHIYUKI; SHIOMI, KAZUAKI; KURIYAMA, ISOKO; TAKAHASHI, YOSHIHIRO; YOSHIDA, HIROMI (International journal of oncology, 2013)
The inhibitory activity of 3 soy isoflavones (daidzein, genistein and glycitein) and their glycosides (daidzin, genistin and glycitin) on mammalian DNA polymerases (pols) and topoisomerases (topos) was investigated. Of the compounds tested, only genistein selectively inhibited human topo II activity and had an IC50 value of 37.5 μM. These isoflavones had no effect on the activity of human topo I; mammalian pols α, β, γ and κ; or on any other DNA metabolic enzyme tested. Thermal transition analysis indicated that genistein did not influence the direct binding to double-stranded DNA. Genistein prevented the proliferation of HCT116 human colon carcinoma cells with an LD50 of 94.0 μM and it halted the cell cycle in G2/M phase. These results suggest that decreases in cell proliferation due to genistein may result from the inhibition of cellular topo II and that genistein, a major soy isoflavone, may be an anticancer food component. The relationship between the structures and these bioactivities of soy isoflavones is discussed.